2022
DOI: 10.3390/antiox11112185
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of the Hydrophilic Extract of Polypodium leucotomos, Fernblock®, against the Synergistic Action of UVA Radiation and Benzo[a]pyrene Pollutant

Abstract: Oxidative stress is a harmful effect induced on the skin by polycyclic aromatic hydrocarbons (PAH), including benzo[a]pyrene (BaP) air pollutants. This effect is amplified by the additive damaging effect of the sun, especially through the UVA light component. Besides being one of the main compounds that make up air pollution, BaP can also be found in tar, tobacco smoke, and various foods. In addition to its direct carcinogenic potential, BaP can act as a photosensitizer absorbing sunlight in the UVA range and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This preclinical study demonstrated the efficacy of Fernblock ® in preventing changes in cellular structure, viability, oxidative stress, and DNA damage. These findings provide strong evidence that Fernblock ® induces the priming of cells, rapidly promoting the activation of repair mechanisms and efficient elimination of oxidized derivatives that appear in the nuclear DNA as a result of sequential exposure to BaP and UVA light [28].…”
Section: Oncodermatologymentioning
confidence: 66%
See 3 more Smart Citations
“…This preclinical study demonstrated the efficacy of Fernblock ® in preventing changes in cellular structure, viability, oxidative stress, and DNA damage. These findings provide strong evidence that Fernblock ® induces the priming of cells, rapidly promoting the activation of repair mechanisms and efficient elimination of oxidized derivatives that appear in the nuclear DNA as a result of sequential exposure to BaP and UVA light [28].…”
Section: Oncodermatologymentioning
confidence: 66%
“…It also inhibits the overproduction of ROS generated by the exposure to photopollution in both melanocyte and keratinocyte cell lines. These findings suggest that Fernblock ® has the potential to mitigate oxidative stress-induced damage and mitochondrial injury resulting from the combined effect of these harmful agents [28].…”
Section: Extrinsic Agingmentioning
confidence: 91%
See 2 more Smart Citations